2019
DOI: 10.1155/2019/1616237
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Myelosuppression due to Progressive Bone Marrow Fibrosis in a Patient with Acute Promyelocytic Leukemia

Abstract: A 34-year-old woman was diagnosed with acute promyelocytic leukemia. Chemotherapy was administered following the JALSG APL204 protocol. Induction therapy with all-trans retinoic acid resulted in complete remission on day 49. She developed coccygeal pain from day 18, which spread to the spine and cheekbones and lasted 5 weeks. She had similar bone pain on days 7–10 of the first consolidation therapy and on days 4–12 of the second consolidation therapy. Oral loxoprofen was prescribed for pain relief. On day 33 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The most common malignant diseases in which generalized BMF is seen are chronic idiopathic myelofibrosis (MF), CML, AML, ALL, MDS, lymphomas and metastatic tumors [23]. Non-malignant causes of BMF include endocrine disorders, autoimmune diseases, vitamin D deficiency and infections (HIV, tuberculosis) [1,2,23]. The identification of BMF is vital in some diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common malignant diseases in which generalized BMF is seen are chronic idiopathic myelofibrosis (MF), CML, AML, ALL, MDS, lymphomas and metastatic tumors [23]. Non-malignant causes of BMF include endocrine disorders, autoimmune diseases, vitamin D deficiency and infections (HIV, tuberculosis) [1,2,23]. The identification of BMF is vital in some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-8, IL-2R and lipocalin-2 are other cytokines that have been suggested to be involved in the pathophysiology of BMF, especially among patients with MF [30]. Genetic studies assessing JAK2 V617, MPL and CALR gene mutations have suggested possible associations with BMF [1]. However, their routine diagnostic value has not been consistent [30].…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 10% to 20% of patients with early bleeding had died, and about 60% of patients develop diffuse intravascular coagulation (DIC). 6,7 Therefore, it is of great significance to identify a therapeutic target of pediatric APL patients.…”
Section: Introductionmentioning
confidence: 99%